DENTAL TREATMENT PLANNING IN DIABETIC PATIENTS - Alin Dumitru Ciubotaru; Carmen-Ecaterina Leferman; Codruța Bădescu; Andreea Ciuca; Daniel Cioloca; Cristiana-Elena Vlad; Monica Cordos; Liliana Foia (Romanian Dental Association for Education, 2023)
Diabetes mellitus, a chronic pathology marked by either insufficient insulin production by the pancreas or the body's ineffectiveness in utilizing produced insulin, is escalating globally, underlining the need for enhanced understanding of the disease and improved dental care for diabetic patients. Individuals with diabetes frequently exhibit oral symptoms and concerns concurrent with the diagnosis of their condition. These symptoms may recur during phases of suboptimal metabolic regulation. Chronic complications of diabetes manifest in the oral cavity over time. Dental practitioners play a pivotal role in the early identification of these oral manifestations. Meticulous dental monitoring and ongoing collaboration with the patient's healthcare team are imperative to mitigate the frequency and severity of enduring oral complications associated with diabetes. This integrated approach is crucial for maintaining oral health in diabetic patients and addressing the broader implications of the disease.